2015
DOI: 10.1042/cs20140695
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory roles of NADPH oxidase, intra- and extra-cellular HSP70 in pancreatic islet function, dysfunction and diabetes

Abstract: The 70 kDa heat-shock protein (HSP70) family is important for a dynamic range of cellular processes that include protection against cell stress, modulation of cell signalling, gene expression, protein synthesis, protein folding and inflammation. Within this family, the inducible 72 kDa and the cognate 73 kDa forms are found at the highest level. HSP70 has dual functions depending on location. For example, intracellular HSP70 (iHSP70) is anti-inflammatory whereas extracellular HSP70 (eHSP70) has a pro-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 138 publications
(125 reference statements)
3
58
0
Order By: Relevance
“…In a recent study, our group observed that the ratio between plasma eHSP70 and cellular iHSP70 in lymphocytes from rats submitted to different loads of acute exercise (an acute stressful situation) can indicate the inflammatory status [34]. Indeed, extracellular to intracellular HSP70 ratio index (H-index) measured in peripheral blood mononuclear cells (PBMC) in relation to serum values has been recently assumed as novel and overall index of immunoinflammatory status of an individual [34,39,105,112]. The rationale for this is that the higher eHSP70 amounts, the more inflammatory signals are coming into play because eHSP70 is proinflammatory in nature.…”
Section: Anti-inflammatory Role Of Intracellular Hsp70mentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, our group observed that the ratio between plasma eHSP70 and cellular iHSP70 in lymphocytes from rats submitted to different loads of acute exercise (an acute stressful situation) can indicate the inflammatory status [34]. Indeed, extracellular to intracellular HSP70 ratio index (H-index) measured in peripheral blood mononuclear cells (PBMC) in relation to serum values has been recently assumed as novel and overall index of immunoinflammatory status of an individual [34,39,105,112]. The rationale for this is that the higher eHSP70 amounts, the more inflammatory signals are coming into play because eHSP70 is proinflammatory in nature.…”
Section: Anti-inflammatory Role Of Intracellular Hsp70mentioning
confidence: 99%
“…Therefore, HSPs may be envisaged as potential therapeutic tools to prevent neurodegeneration by avoiding protein aggregation processes, thus reducing the toxicity of such oligomers [170]. However, more studies are required to identify the specific signaling pathways and routes of administration of HSP70 to avoid possible harmful effects because, if HSP70 is not accurately introduced inside brain cells, it could remain within the extracellular space, where eHSP70s is a pro-inflammatory by virtue of what the binding to TLR2 and TLR4, at least in other cells, may exert [62,112]. Still in support of a major role of HS response for normal brain function, numerous studies have shown that the plant polyphenol resveratrol (3,5,4′-trihydroxystilbene) may extend the lifespan of several species, preventing age-related diseases beside possessing anti-inflammatory action.…”
Section: Suppression Of the Heat Shock Response In Agerelated Degenermentioning
confidence: 99%
See 3 more Smart Citations